2006
DOI: 10.2471/blt.05.023903
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in Senegal

Abstract: Objective The improvement of obstetric services is one of the key components of the Safe Motherhood Programme. Reviewing maternal deaths and complications is one method that may make pregnancy safer, but there is no evidence about the effectiveness of this strategy. The objective of our before and after study is to assess the effect of facility-based maternal deaths reviews (MDR) on maternal mortality rates in a district hospital in Senegal that provides primary and referral maternity services. Methods We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…In places where establishment of maternal mortality audits has led to improved quality of obstetric care, the success has been particularly attributed to strong leadership and accountability of both health providers and key decision makers [7,11,25,26]. Our findings recommend a more responsive health system from the level of the ministry of health down to the grass root levels.…”
Section: Discussionmentioning
confidence: 81%
“…In places where establishment of maternal mortality audits has led to improved quality of obstetric care, the success has been particularly attributed to strong leadership and accountability of both health providers and key decision makers [7,11,25,26]. Our findings recommend a more responsive health system from the level of the ministry of health down to the grass root levels.…”
Section: Discussionmentioning
confidence: 81%
“…The situation has been found to be similar in India, where a maternal death review at the community level is vital in making maternal deaths more visible to community members and policy-makers [12]. Many African countries also undertake maternal death reviews at facility level [24]. One African study concluded that facility-based MDR can be combined with community verbal autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that recommendations resulting from the audit sessions were poorly implemented because of a lack of human and material resources and insufficient staff and senior management commitment [ 13 , 14 ]. Conversely, in other studies where recommendations were implemented and evaluated, reductions in maternal mortality, the case fatality rate [ 50 , 51 ], the incidence of uterine rupture, obstetric hemorrhage and the number of women with severe maternal complications were observed [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%